Systemic doxycycline as an adjunct to nonsurgical periodontal therapy in diabetic patients with periodontitis: a systematic review and meta-analysis - Zheng Zhang; Zheng Zhang; Zhenyu Zhang; Guoquan Zhang (Frontiers in Physiology, 2025)
BackgroundRecent studies that investigated the effects of systemic doxycycline as an adjuvant to scale and root planing (SRP) in the treatment of diabetic periodontitis have yielded controversial results. The aim of this meta-analysis is to evaluate the effect of systemic doxycycline as an adjunct to SRP against SRP alone for improving clinical outcomes of periodontitis in diabetic individuals.MethodsA systematic literature search was performed using PubMed, Cochrane library, China National Knowledge Infrastructure (CNKI), and VIP Data from the beginning of the database until March 2024. For probing depth (PD), clinical attachment level (CAL), plaque index (PI), gingival index (GI), and bleeding on probing (BOP), mean difference (MD) and the 95% confidence interval (CI) were computed. Heterogeneity was assessed using the Q test and the I2 statistic. Evaluation of publication bias was conducted using Egger’s and Begg’s tests.ResultsA total of 12 articles were included for meta-analysis. No statistically significant difference was indicated in the improvement of PD, CAL, PI and GI between a treatment group receiving SRP combined with short-term antimicrobial dose doxycycline and controls receiving SRP alone. However, short-term antimicrobial dose doxycycline plus SRP significantly reduced BOP by 8.14% (95%CI 2.23–14.05) at 3 months. Furthermore, after the adjunctive use of long-term sub-antimicrobial dose doxycycline, significant reductions in GI (MD: 0.72, 95% CI: 0.34–1.10) and BOP (MD: 12.8, 95% CI: 0.24–25.36) were observed at 3 months. The robustness of the results was further confirmed by sensitivity analysis, despite the truth that significant heterogeneity was found among the included studies.ConclusionGingival inflammation in diabetic patients can be reduced more successfully by SRP combined with systemic doxycycline than by SRP alone, but this is insufficient in preventing periodontal tissue destruction.